1993
DOI: 10.2527/1993.7171688x
|View full text |Cite
|
Sign up to set email alerts
|

Body dimensions and carcass measurements of cattle selected for postweaning gain fed two different diets

Abstract: Genetic and phenotypic parameters among nine body dimensions and two measures of growth rate were estimated from measurements on 709 Angus and Hereford bulls and heifers born in 1984 and 1985. Height and width at hips, height at withers, body length, girth, head length and width, muzzle width, and cannon bone circumference were measured at weaning and again after 168-d postweaning gain tests. The cattle were from the final two calf crops of a 20-yr study to examine the response to selection for postweaning gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
3
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 0 publications
7
21
3
2
Order By: Relevance
“…However, the maintenance of birth growth advantage to later ages (Adu and Ngere, 1979;Tuah and Baah, 1985), as observed herein, is supported by the maternal ability of ewes when suckling heavier lambs which tend to be male (Newman et al, 1993) or of lamb's subsequent ability to eat grass. These differences between male and female lambs were similar to those reported in beef cattle (Gilbert et al, 1993;Afolayan et al, 2002a,b). In those reports, steers were heavier, taller and bigger in girth; more muscled but with less fat compared to heifers both at weaning and post-weaning ages.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the maintenance of birth growth advantage to later ages (Adu and Ngere, 1979;Tuah and Baah, 1985), as observed herein, is supported by the maternal ability of ewes when suckling heavier lambs which tend to be male (Newman et al, 1993) or of lamb's subsequent ability to eat grass. These differences between male and female lambs were similar to those reported in beef cattle (Gilbert et al, 1993;Afolayan et al, 2002a,b). In those reports, steers were heavier, taller and bigger in girth; more muscled but with less fat compared to heifers both at weaning and post-weaning ages.…”
Section: Discussionsupporting
confidence: 89%
“…However, feedlot trials with beef cattle crossbreds (Rutley et al, 1995) showed that weight, height, fat depth and visual muscle score (score developed by McKiernan, 1990) could be sufficient to describe variation in feedlot performance of the most economically important traits (average daily gain, carcass weight, fat depth and saleable beef yield). In the same species, objective body dimensions and measures of muscular development were shown to serve either to supplement body weight as a measure of productivity (Afolayan et al, 2002a,b) or as predictors of some less visible characteristics (Gilbert et al, 1993). In addition, body measurements could be used to predict live weight fairly well in the situation where weighbridges are not available (Berge, 1977;Buvanendran et al, 1980;Goonerwardene and Sahaayuraban, 1983).…”
mentioning
confidence: 99%
“…Few studies included additional body measurements like hip height and body length mostly at post-weaning (Gilbert et al, 1993;Vargas et al, 2000). In this study, the direct heritability for weaning weight (18%, Table 2) was lower than both the unweighted (35% and 27%) and weighted (31% and 24%) mean estimates reviewed from over 170 papers (Koots et al, 1994a).…”
Section: Genetic Effectsmentioning
confidence: 66%
“…However, higher estimates were obtained for weaning height in the studies of Vargas et al (2000) on a single breed (Brahman) measured at a much older age (18 months) and Gilbert et al (1993) on Hereford and Angus breeds. Apart from the work of Gilbert et al (1993) that provided heritability estimates for weaning and post-weaning length as an additional body dimensional trait, the mostly moderate estimates for body length (19 to 25%) and girth (9 to 32%) from weaning (250) day to 600-day of age herein represents the first Australian estimates for beef cattle breed types for genetic description of animal size. Gutierrez and Goyache (2002) were of the opinion that standard breed conformation described by skeletal and muscular development could be effectively used to evaluate the animal's productive ability.…”
Section: Genetic Effectsmentioning
confidence: 92%
See 1 more Smart Citation